Health and Beauty : A Book for Girls - Foley, Elizabeth; Cocker, Edith A. (London : The Health & Cleanliness Council)
1939-10 1939 1930s 27 pages ; illustrations For a muddy complexion. — Eat plenty of green vegetables, not too many sugary foods. Wash all over daily, finishing with a hard rub. Meanwhile keep your inside clean; it needs a good clear out daily. For "saltcellars" in your neck. — Take deep breathing exercises, beginning with a few three or four times a day, and try to get into the habit of "holding your neck well into the collar," shoulders down, and breathing fully without forcing. The hollows will soon fill up. Brisk towelling in a circular motion will help also. Dandruff or scurf. — First wash your hair, rinse, and rub in a little olive oil or toilet lanolin and brush thoroughly; repeat every few days. Dry hair. — Treat as for dandruff, but before shampooing make a point of leaving a generous application of oil on for half an hour. Then wash thoroughly with a good shampoo, dry and massage in a little lanolin and brush well. Greasy hair. — Allow air and sun to play on your hair and apply brush and finger massage. Shampoo frequently with a good shampoo. Itching scalp. — Brush well down on to the scalp night and morning, and rub a little boracic lotion into the roots. To keep fair hair from fading. — Dry it in the sun whenever possible. Waving. — Hot irons injure the hair. It is better to put it into pliable curlers that will not strain it. Careful attention to daily scalp massage with frequent shampooing has a tendency to produce a natural wave. Printed in Great Britain by Billing and Sons Ltd., Guildford and Esher 177/5/8/4